2017
DOI: 10.22159/ijap.2017v9i5.20847
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antityrosinase and Antioxidant Potential of Zinc Oxide Nanoparticles Synthesized From the Brown Seaweed-Turbinaria Conoides

Abstract: Objective: The present study was designed to evaluate the antioxidant and antityrosinase properties of zinc oxide nanoparticles (ZnO-NPs) synthesized from brown seaweed Turbinaria conoides.Methods: Zinc Oxide Nanoparticles were synthesized from the hydroethanolic extract of Turbinaria conoides. Ultraviolet-Visible Spectrophotometric analysis was performed to confirm the formation of ZnO-NPs. Size, morphology and elemental composition of ZnO-NPs were analysed using SEM-EDAX. The antioxidant activity of the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
3
1
Order By: Relevance
“…The results of the tyrosinase inhibitory screening in this study for AgNPsarebetter than those obtained from tyrosinase inhibitory screening for AgNPs and ZnONPsfrom extracts of Artemisia annua and seaweed-turbinaria conoides, which gave 40% (100mg/mL) and 50% (100μg/mL) respectively [13,14]. The results of tyrosinase inhibitory activity of AgNPs (20.83 μg/mL) was also better than those we had reported for ZnO-NPs (obtained from aqueous leaf extracts of A.laxiflora) with IC50 of66.28μg/mL [14] and AgNPs (obtained from aqueous leaf extracts of Euphorbia sanguine) with IC50 of 71.96µg/ml [34].The improved tyrosinase inhibition prompted further investigation of the kinetics of the inhibition and mode of inhibitor-tyrosinase interaction.…”
Section: Fig 7: Tyrosinase Inhibitory Activity Of Agnpscontrasting
confidence: 58%
See 2 more Smart Citations
“…The results of the tyrosinase inhibitory screening in this study for AgNPsarebetter than those obtained from tyrosinase inhibitory screening for AgNPs and ZnONPsfrom extracts of Artemisia annua and seaweed-turbinaria conoides, which gave 40% (100mg/mL) and 50% (100μg/mL) respectively [13,14]. The results of tyrosinase inhibitory activity of AgNPs (20.83 μg/mL) was also better than those we had reported for ZnO-NPs (obtained from aqueous leaf extracts of A.laxiflora) with IC50 of66.28μg/mL [14] and AgNPs (obtained from aqueous leaf extracts of Euphorbia sanguine) with IC50 of 71.96µg/ml [34].The improved tyrosinase inhibition prompted further investigation of the kinetics of the inhibition and mode of inhibitor-tyrosinase interaction.…”
Section: Fig 7: Tyrosinase Inhibitory Activity Of Agnpscontrasting
confidence: 58%
“…Biogenic silver obtained from extracts of Hovenia dulcis fruit extract [13] and zinc oxide nanoparticles obtained from brown seaweed of Turbinaria conoides [14] have been reported to exhibit tyrosinase inhibition. Tyrosinase inhibition is an efficient mechanism in the treatment of skin diseases of hyperpigmentation such as melasma, freckles, age spots and senile lentigo [15].…”
Section: Mimosamentioning
confidence: 99%
See 1 more Smart Citation
“…23 Moreover, Dani and Dhawan 24 and Malekirad et al 25 reported that Zn is a protecting antioxidant due to its ability to bring the malondialdehyde (MDA) levels to near normal levels. Additionally, Raajshreer and Durairaj 26 revealed that their synthesized ZnO NPs possess antioxidant activity with respect to mechanisms of both reducing activities and free radical scavenging.…”
Section: Introductionmentioning
confidence: 99%